Conserving space by autologous transplantation of O.D 48 to dental organ space 46: A case report - Santana , Belinda Pérez; Landeros , Edgar Miguel Raúl Hernández; González , Rubén Alberto Bayardo; Salas , Luz Elena Nápoles; González , Carolina Solorio; Santana , Sabrina del Rosario Pérez; Taylor , Saralyn López y; Palomera , Olga Rocío Manzo; Sánchez , Ana Bertha Olmedo; Cobos , Rosa Patricia Gómez (Seven Editora, 2023)
Autologous transplantation is a radical, conservative and rehabilitative surgical procedure performed in the face of the loss of a dental organ. It consists of extracting a dental organ from its socket and reimplanting it in that of another, in the same patient, who must meet characteristics such as adequate age, good systemic health, hygiene, oral health, cooperation and an adequate recipient socket to predict its success according to Vinitzky Brener I. et al.. DOI:https://doi.org/10.56238/interdiinovationscrese-035